2022
DOI: 10.1002/jobm.202100623
|View full text |Cite
|
Sign up to set email alerts
|

Engineered green nanoparticles interact withNigrospora oryzaeisolated from infected leaves ofArachis hypogaea

Abstract: Oilseed crop diseases are a major concern around the world, particularly in India. The synthetic fungicides not only kill the pathogen, but they also harm the host plant and beneficial microbes and on continuous usage, they decrease the soil fertility. To overcome this problem, green nanotechnology has been a greater alternative with promising benefits. The green synthesized nanoparticles from the extract of various plant parts are an effective remedy for killing the pathogens without affecting the host plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…N. oryzae and N. sphaerica can often infect the same species of plant, such as Arachis hypogaea and Vaccinium corymbosum [ 49 , 50 , 51 , 52 ]. As for chrysanthemums, a widespread disease caused by N. sphaerica has been found in chrysanthemum growing areas [ 53 ], and in this study we found that N. oryzae is also a pathogen of chrysanthemum.…”
Section: Discussionmentioning
confidence: 99%
“…N. oryzae and N. sphaerica can often infect the same species of plant, such as Arachis hypogaea and Vaccinium corymbosum [ 49 , 50 , 51 , 52 ]. As for chrysanthemums, a widespread disease caused by N. sphaerica has been found in chrysanthemum growing areas [ 53 ], and in this study we found that N. oryzae is also a pathogen of chrysanthemum.…”
Section: Discussionmentioning
confidence: 99%